Spatiotemporal Variation of Leaf Area Index and Its Response to Climatic Factors in Ulanqab City - Huang Yan; Song Haiqing; Sun Xiaolong; Li Yunpeng; Hu Qi (Shuitu baochi tongbao)
[Objective] The dynamic change of leaf area index (LAI) and its response to climatic factors in Ulanqab City were studied in order to provide a scientific basis for rational resource allocation and ecological conservation. [Methods] Based on the Copernicus Climate Change Service PROBA-V LAI data and meteorological data from July to August during the period of 2000—2019, the spatiotemporal variation of LAI and its relationship with temperature, precipitation, and soil moisture in Ulanqab City were explored using linear trend analysis, coefficient of variation analysis and correlation analysis. [Results] ① Average LAI showed a fluctuating upward trend at a growth rate of 0.01 per year in Ulanqab City during the study period. Significant differences were found in the spatial distribution of LAI, which was characterized by high LAI in the southeast and low LAI in the northwest. ② Although 88.3% of the study area showed an increasing trend for LAI, the change of LAI was relatively unstable during the study period. A significant increasing trend was found in most of Xinghe County, the east of Fengzhen City, the west of Liangcheng County, the southwest of Siziwang Banner, and the central and northern parts of Chahar Right Middle Banner, while a slowly increasing or decreasing trend was found in most areas of Houshan Mountain in the north of Yinshan Mountain. ③ LAI showed a significant negative correlation with temperature, and a highly significant positive correlation with precipitation and soil moisture. The correlation of LAI with soil moisture was higher than that of precipitation and temperature. ④ No significant difference was found in the spatial distribution of correlation coefficients between LAI and temperature, precipitation, and soil moisture. Most areas had negative correlations between LAI and temperature, with 45.4% of the study area showing significant negative correlations. LAI had significant positive correlations with precipitation and soil moisture, and the area of significant correlation between LAI and soil moisture was larger than that of precipitation. [Conclusion] During 2000—2019, the LAI of vegetation in Ulanqab City showed an increasing trend and obvious spatial heterogeneity. Soil moisture was the decisive factor affecting vegetation growth.